Impelementation of Whistleblowing System at Institution Y - Roy Mangara Tahi Siagian; Widya Perwitasari (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study evaluates the effectiveness of the whistleblowing system (WBS) implemented by Institution Y, utilizing the criteria outlined in the 2008 Whistleblowing System Guidelines issued by the National Committee on Governance Policy (KNKG). A case study methodology was employed, incorporating a thematic analysis approach. The research utilized both primary and secondary data sources. Primary data were collected through interviews with members of the WBS management team, investigators, and other relevant personnel within Institution Y. Secondary data comprised the institution’s standard operating procedures (SOPs) and pertinent gubernatorial regulations from ABC Province. The findings indicate that employees at Institution Y demonstrate a strong commitment to reporting suspected violations and uphold the confidentiality of whistleblowers, primarily through anonymous reporting mechanisms. Upon receipt of a report, the WBS team assesses the adequacy of preliminary evidence to determine whether the report warrants further action. Limited human resources and the absence of incentives for reporters are weaknesses in the implementation of WBS at Institution Y. Nonetheless, the whistleblowing system at Institution Y is found to be operating effectively.